PENTINGNYA ITIKAD BAIK DALAM PERJANJIAN TUKAR TAMBAH KENDARAAN RODA EMPAT PADA SHOWROOM ZIKRI DI SAMARINDA - Ariza Ramadani (Journal of Law ( Jurnal Ilmu Hukum ), 2014)
ABSTRACTBoth parties must be acting in good faith in carrying out an agreement. There are times when good faith has been fully carried out and considered, but the implementation of the agreement is still in a deadlock (deadlock). This is where attention is required in the direction of compliance so that an event can be resolved satisfactorily. Of course, as is the case with all the goods things that contain award (waardering), compliance is not likely to result in a settlement satisfactory event every human person, but always is not absolute (relatief), which is worth in the thoughts and feelings of people who are in charge of completing a events, such as Judge or the Administration after watching all the factors, which can be used in a natural state of mind and feelings of the people.Occur close relationship between the doctrine of good faith in the implementation of the agreement and the theory of confidence at the time of the agreement. Good faith (Article 1338, paragraph 3) and decency (Article 1339) is generally mentioned in the same breath, if the judge after testing the appropriateness of an agreement can not be implemented then it means that the agreement was contrary to public order and decency. Agreement is not only determined by the parties in the formulation of the agreement but also by good faith and decency, so in good faith and decency were also specify the content of the agreement. With such an agreement, especially treaty Rates plus moving objects when the vehicle type is not implemented in good faith (bad faith) that the agreement is contrary to public order and morals and norms applicable law.